Procurement and Service Delivery : An Overview of Efforts to Improve Governance of Public Procurement at Local Levels in South Asia - World Bank (World Bank, Washington, DC, 2013)
Over the past decade, the overly centralized governance structures commonly found across South Asia have begun to change, with program and fiscal responsibility being devolved to local level government authorities and community-based organizations. This has led to greater participation of ordinary citizens in governance and public decision-making. The move to localize decision-making creates enormous opportunities for increasing the effectiveness of public spending since it creates the potential for establishing direct accountability of governance mechanisms to citizens. It also raises a number of significant challenges in ensuring that public funds are spent effectively at the local level, and provokes important new questions regarding the manner by which governments can maintain oversight over the quality of assets. This paper provides an overview of the activities supported under the project, with the aim of contributing to a broader perspective on improving governance and service delivery at the local level. The paper is divided into three parts. In part one the authors explore the challenges of spending money effectively at the local level, with a special focus on the governance challenges that exist in public procurement. In part two, the authors explore different approaches to addressing those challenges by discussing innovative work that has taken place with the support of the Project in the areas of regulation, contracting, transparency, and accountability. In part three, the authors analyze some broader themes and key questions that remain to be addressed while developing a strategic research and operational agenda around local level procurement.